Benarkah anak prasekolah sudah mampu mengambil perspektif dalam perilaku prososial? - Putri Arlanda Permatasari; Hendriati Agustiani; Amir Sjarif Bachtiar (Jurnal Psikologi Sosial, 2021)
Previous studies suggested that preschoolers have already behaved prosocially. However,there is a possibility that such insight cannot be generalized since there is a conflictingassumption between different theoretical perspectives. The research aimed to explorewhether pre-schoolers’ perspective-taking in the context of prosocial behavior had developed.Our participants were 25 preschoolers who were 5-6 years old. The result showed that fromthe three types of perspective-taking, which were perceptual, cognitive, and affectiveperspective-taking, affective perspective-taking was undeveloped optimally among themajority of pre-schoolers. They had difficulty when identified others’ emotions in the context,especially in prosocial situations. For cognitive perspective-taking, preschoolers understoodother people’s thoughts, intentions, and motives, but only when the environmental cues weresimple. When the situation was more complex, their efforts to understand other people’sthoughts, intentions, or motives resulting in different understanding about the situations.Preschoolers’ ability to do perceptual perspective-taking had developed. They could shift theirperceptual perspective-taking from themselves to other perceptual perspective-taking. Theresults can be used as a reference for developing intervention programs to improveperspective-taking skills in contexts of prosocial behavior in preschool children.